Transit oriented development in the South African context: an analytical review of Johannesburg's recent urban policy and strategy - Bickford, Geoffrey (Department of Civil Engineering, 2016)
Globally, the growth trend of cities over the past century has been one of rapid outward expansion. It is no coincidence that this growth has coincided with the rapid uptake of the private automobile. There is now unequivocal evidence that the two phenomena are deeply interrelated. South Africa has not escaped these influences, but the picture is slightly nuanced. Apartheid spatial planning has defined the urban experience in contemporary South Africa. Many black people still live extraordinarily far from places of economic opportunity and are forced to commute using dissatisfactory public transport services over long distances, for many hours at high personal and household costs. Confronting the apartheid spatial pattern has consistently been at the forefront of urban policy in democratic South Africa. Transit Oriented Development (TOD) has gained much traction globally as a concept which can provide strengthened alignment between public transport systems and urban development patterns, fostering more sustainable and liveable city fabrics. TOD is increasingly being drawn on in South Africa as an approach to more sustainable and socially integrated development, evidenced through its explicit inclusion in the National Development Plan which calls for the 'internationally accepted principles' of TOD to be applied. The overarching aim of the research is to interrogate how TOD is being understood in a South African context. The research seeks to bring the range of TOD international and local literature together to provide a thorough literature review on the topic. In depth South African insight will be provided by drawing on the case of Johannesburg's recent urban policy and strategy and an associated stakeholder interview analysis in an attempt to move beyond the rhetoric and gain important insights from potential TOD implementation stakeholders. Key research questions are: what are the lessons on offer from international experience?; to what extent is there evidence that these have been applied in developing a TOD understanding in Johannesburg specifically and South Africa more generally?; and ultimately taking into consideration the international experience, local insights and context, how is TOD being understood in South Africa? The research is primarily literature review based. Thus, existing international literature detailing TOD principles, approaches, experiences and outcomes as well as the limited South African literature on the topic, including policy and strategy documents are drawn on to build and understanding of the details of the concept and how it is being unpacked in South Africa. A case study of the City of Johannesburg is carried out to develop a focused understanding of how TOD is being understood in South Africa. The case study comprises a literary review of the policy, strategy and planning documents of the municipality over the past decade. The literature review is supplemented by a stakeholder analysis of identified potentially important stakeholders in a TOD agenda. Fifteen stakeholders were contacted for interviews and eleven (n=11) interviews were eventually conducted. The combination of the international and South African literature, the Johannesburg policy analysis and the stakeholder insights are argued to provide sufficient information to answer the research questions.